Developing Teaching Skills for Teachers in Remote Areas: Implementing Community Service Programs - Hanafiah, Hanafiah; Sartinayanti, Sartinayanti; Sukmayadi, Dodi; Muhajir, Muhajir; Ekawati, Mutmainna (PT Inovasi Pratama Internasional, 2025)
This qualitative study examines the role of community service programs in enhancing teaching competencies for educators in remote regions. Drawing on case studies from Indonesia, Tanzania, and the United States, the research highlights how collaborative, community-driven initiatives address systemic challenges such as resource shortages, professional isolation, and inequitable access to training. Findings emphasize the importance of localized pedagogical strategies, sustained mentorship, and multi-stakeholder partnerships in fostering teacher resilience and improving educational outcomes. Through in-depth interviews with teachers and program facilitators, as well as participant observations, this study reveals that effective community service programs not only enhance teaching skills but also promote a sense of belonging and commitment among educators. The data indicates that when teachers are actively involved in their communities, they are more likely to adopt innovative teaching practices that resonate with local cultures and needs. The implications of this research suggest that policymakers should prioritize funding and support for community service initiatives as a viable strategy for professional development in remote areas. By leveraging local knowledge and resources, these programs can create sustainable improvements in education quality, ultimately leading to better student performance and community engagement.